A Half Century of Occupation : Israel, Palestine, and the World's Most Intractable Conflict - Shafir, Gershon (California University of California Press, 2017)
"The Israel-Palestine conflict is one of the most polarizing and long-lived confrontations in the world. Tearing communities apart in Israel and Occupied Palestine, with repercussions across the globe, Israel's "temporary" occupation turns a half century old in 2017. This timely and provocative book offers a background history and context for general readers and covers the major turning points of the conflict. Expertly detailing the political, diplomatic, and legal dimensions of the struggle, Gershon Shafir examines the effect of the colonization of occupied territories on Israel's democracy and offers compelling reasons and possibilities for ending the occupation now."--Provided by publisher
Include Bibliography and Index
Keywords: Arab-Israeli Conflict 1993 Peace -- Middle East Palestine -- Diplomatic Relations